The application of project management theory in hospital management: Bibliometric analysis based on web of science database - Liu, Yuchi; Shafiei, Mohd Wira Mohd (Edelweiss Applied Science and Technology, 2025)
This investigation analyzes the incorporation of theoretical frameworks in project management within the context of hospital administration through a bibliometric evaluation of publications in the Web of Science from 2014 to 2024 using CiteSpace. An analysis of contributions by 7,020 researchers in 96 countries across 426 publications identified Jeffrey Braithwaite as one of the notable contributors, while the top institutions in this field included Harvard University and the University of London. Findings reflect an evolution in methods in project management from conventional waterfall methods to agile and mixed methods. Keyword analysis emphasized an increased focus on improving quality, implementation, and evidence-based practice, indicating a greater emphasis on leadership and evidence-based practice between 2020 and 2024 compared to systems and management themes from 2014 to 2018. Highly cited publications included JAMA and BMC Health Services Research. Conclusion: Project management in hospital contexts has immense potential for optimizing resources, improving service provision, and enhancing patient outcomes while reducing organizational costs in complex healthcare systems. Practical Implications: Findings reflect an emerging interdisciplinary framework that integrates aspects of nursing, public policy in healthcare, nursing management, and patient safety with value-based healthcare programs focusing on improving quality, efficiency, and outcomes as core objectives.